Valency over Time Diachronic Perspectives on Valency Patterns and Valency Orientation - Luraghi, Silvia; Roma, Elisa (Trends in Linguistics. Studies and Monographs [TiLSM], 2021)
The papers collected in this book are devoted to verbal valency, and share a diachronic perspective, by either discussing changes in the behavior of verbs or discussing verbal valency at different historical stages of specific languages. They provide new data for research on valency patterns and on changes in valency orientation, verbal voice, and related constructions.